Models of cuspy triaxial stellar systems - II. Regular orbits - Muzzio, Juan Carlos (2013)
n the first paper of this series we used the N-body method to build a dozen cuspy (γ ≃ 1) triaxial models of stellar systems, and we showed that they were highly stable over time intervals of the order of a Hubble time, even though they had very large fractions of chaotic orbits (more than 85 per cent in some cases). The models were grouped in four sets, each one comprising models morphologically resembling E2, E3, E4 and E5 galaxies, respectively. The three models within each set, although different, had the same global properties and were statistically equivalent. In the present paper we use frequency analysis to classify the regular orbits of those models. The bulk of those orbits are short-axis tubes, with a significant fraction of long-axis tubes (LATs) in the E2 models that decreases in the E3 and E4 models to become negligibly small in the E5 models. Most of the LATs in the E2 and E3 models are outer LATs, but the situation reverses in the E4 and E5 models where the few LATs are mainly inner LATs. As could be expected for cuspy models, most of the boxes are resonant orbits, i.e. boxlets. Nevertheless, only the (x, y) fishes of models E3 and E4 amount to about 10 per cent of the regular orbits, with most of the fractions of the other boxlets being of the order of 1 per cent or less.